Atmospheric Drivers of Melt on Larsen C Ice Shelf: Surface Energy Budget Regimes and the Impact of Foehn. Issue 17 (31st August 2020) - Elvidge, Andrew D.; Kuipers Munneke, Peter; King, John C.; Renfrew, Ian A.; Gilbert, Ella
Abstract: Recent ice shelf retreat on the east coast of the Antarctic Peninsula has been principally attributed to atmospherically driven melt. However, previous studies on the largest of these ice shelves—Larsen C—have struggled to reconcile atmospheric forcing with observed melt. This study provides the first comprehensive quantification and explanation of the atmospheric drivers of melt across Larsen C, using 31‐months' worth of observations from Cabinet Inlet, a 6‐month, high‐resolution atmospheric model simulation and a novel approach to ascertain the surface energy budget (SEB) regime. The dominant meteorological controls on melt are shown to be the occurrence, strength, and warmth of mountain winds called foehn. At Cabinet Inlet, foehn occurs 15% of the time and causes 45% of melt. The primary effect of foehn on the SEB is elevated turbulent heat fluxes. Under typical, warm foehn conditions, this means elevated surface heating and melting, the intensity of which increases as foehn wind speed increases. Less commonly—due to cooler‐than‐normal foehn winds and/or radiatively warmed ice—the relationship between wind speed and net surface heat flux reverses. This explains the seemingly contradictory results of previous studies. In the model, spatial variability in cumulative melt across Larsen C is largely explained by foehn, with melt maxima in inlets reflecting maxima in foehn wind strength. However, most accumulated melt (58%) occurs due to solar radiation in the absence of foehn. A broad north‐south gradient in melt is explained by the combined influence of foehn and non‐foehn conditions. Plain Language Summary: The recent rapid retreat and collapse of ice shelves on the east coast of the Antarctic Peninsula is known to be primarily a result of enhanced surface melt due to climate warming and changing atmospheric circulation patterns. However, previous studies have struggled to reconcile observed melt patterns with meteorological conditions. Here we provide the first quantification and explanation of the atmospheric drivers of melt across Larsen C, the largest ice shelf on the Antarctic Peninsula. We find that variability in melt across Larsen C is primarily governed by mountain winds known as foehn, with melt maxima in ice shelf inlets coinciding with the strongest foehn winds. Foehn air is usually much warmer than the ice below, resulting in elevated heating and melting of the ice, the intensity of which increases with increasing wind speed. However, in rare cases where the foehn air is not significantly warmer than the ice, the relationship between melt and foehn wind speed reverses, which explains the seemingly contradictory results of previous studies. While foehn causes the highest melt rates, non‐foehn‐driven melt is more common and, via summertime solar heating, is responsible for most of the accumulation of melt across the ice shelf as a whole. Key Points: Spatial variability and maxima in Larsen C melt are chiefly due to foehn‐driven sensible heating, though most melt is due to solar radiation Low static stability reverses the usual positive correlation between melt and foehn wind speed, explaining conflicting results in previous studies A high‐resolution atmospheric model capably reproduces melt patterns across Larsen C but has notable biases in the surface radiative fluxes